ISLAMIC VALUE INTEGRATION: REDEFINING EDUCATION AT MTs NEGERI PAREPARE - Arfian Alinda Herman; Raden Ajeng Siti Dwi Wulandari Suparyo; Musdalifa Muhtar; Nur Syila Saqinah; Mulyani B; Nabila Putri; M, Nuraini; Hilda; Sri Mulianah (Prodi Pendidikan Agama Islam, 2025)
This study aims to find, study, know, and provide information about the integration of Islamic values in learning Islamic religious education. This study uses a qualitative research method by seeking data in the field or at a predetermined location by conducting interviews with one of the Islamic religious education teachers at MTsN Parepare. The results of the research show that, Umi Uhbiyat, Ahmad D. Marimba said that Islamic education is a physical and in-depth direction in view of strict Islamic rules, towards the production of main characters as indicated by Islamic guidelines. The integration of Islamic values in the learning of Islamic religious education is a process of unifying and aligning Islamic principles with the learning approaches used in the educational context. The main objective is to ensure that Islamic religious values are not only understood theoretically, but are also applied practically in the daily lives of students. The conception of the development of Islamic education in educational institutions involves several important aspects, including; curriculum, teaching methods, personality development, learning environment, the role of the teacher, integration with general education. The deductive method, inductive method, and problem solving methods are some learning strategies that can be utilized in integrating human and divine values. The conclusions from this study, hopefully, can be a reference as well as information for future researchers to study more deeply about the integration of Islamic values in learning Islamic religious education and this research can be a charity for researchers.